Rheumatoid arthritis and dynamic exercises: A case study - Nayak, Disha; Sheth, Megha (Indian Journal of Case Reports, 2020)
Rheumatoid arthritis (RA) is a painful and progressive condition. It leads to progressive joint damage which may lead to difficulties in the activity of daily living (ADL) and reduced quality of life (QoL). The aim of this case report, of a 50-year-old RA patient, was to see the improvements in ADLs, pain, aerobic capacity, and QoL. Dynamic exercises in form of resisted and aerobic exercises were given to the patient for 9 months and patient was evaluated at the end of 1, 3, 6, and 9 months. QoL was measured using health assessment questionnaire, pain was measured using visual analog scale and 6-min walk test was used to measure peak VO2. Improvement was seen in pain, QoL, and aerobic capacity in all measurements.